Peningkatan keterampilan masyarakat Desa Rumbio Kabupaten Kampar melalui pengolahan Jahe Merah - Evi Sribudiani; Sonia Somadona; Pebriandi Pebriandi; Defri Yoza; Viny Volcherina Darlis (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
The people of Rumbio Village are people with an average profession as farmers. The people of Rumbio Village have an economic level at the middle to lower level and need special attention from the government. One way to improve the economic level of the Rumbio village community is by forming their skills in post-harvest processing of agricultural products. This skill is needed for processing agricultural products in this case red ginger. based on this, a community service activity entitled